A rapid-response near-infrared fluorescent probe with a large Stokes shift for senescence-associated β-galactosidase activity detection and imaging of senescent cells. (November 2020) - Qiu, Wenjing; Li, Xiaokang; Shi, Donglei; Li, Xinming; Gao, Ying; Li, Jinwen; Mao, Fei; Guo, Yuan; Li, Jian
Abstract: Detection of senescence-associated β-galactosidase (SA-β-gal) activity at an increased lysosomal pH is one of the most reliable approaches for probing senescent cells. Herein, we developed a novel near-infrared fluorescent probe (KSL0401 ) for sensing SA-β-gal activity and applying in visualization of aging. This probe was designed by connecting a cleavable d -galactose residue to the coumarin-dicyanoisophorone hybrid fluorophore KSL0401-OH via a β-glycosidic bond. The spectral properties of KSL0401 reaction with β-gal were measured in aqueous solution at pH 6.0, and a remarkable enhancement of fluorescence emission at 706 nm was observed, along with a visible colorimetric change. Probe KSL0401 was highly selective and sensitive to SA-β-gal, and displayed large Stokes shift (218 nm) and good biocompatibility. Moreover, it exhibited extremely rapid response to β-gal within 80 s, which surpassed most of the reported SA-β-gal probes. Additionally, KSL0401 also enabled to detect the endogenous SA-β-gal activity in living cells, and distinguish between senescent cells and non-senescent cells and qualify the degree of aging. These findings demonstrate that KSL0401 is a potential detection tool in the imaging research of aging. Graphical abstract: A novel NIR fluorescent probe KSL0401 was applied for accurate SA-β-gal activity detection and imaging of senescent cells. Image 1 Highlights: A coumarin-dicyanoisophorone based NIR fluorescent probe KSL0401 was developed for SA-β-gal activity detection. KSL0401 exhibited large Stokes shift (218 nm), extremely rapid response (80 s), high selectivity and high sensitivity. KSL0401 was successfully applied to monitoring endogenous SA-β-gal activity and evaluating the degree of aging.